Dielectric properties of CuInP₂S₆ crystals under high pressure - Shusta, V.S.; Prits, I.P.; Guranich, P.P.; Gerzanich, E.I.; Slivka, A.G. (Condensed Matter Physics, 2007)
Dielectric properties of CuInP₂S₆ layered crystals in the range of ferrielectric phase transition are studied under hydrostatic pressure. The pressure dependence of the phase transition temperature testifies to the phase transition being of the order/disorder type. The (p, T) phase diagram of CuInP₂S₆ crystals has been constructed.